2016
DOI: 10.1097/nnr.0000000000000135
|View full text |Cite
|
Sign up to set email alerts
|

Do You Know My Child? Continuity of Nursing Care in the Pediatric Intensive Care Unit

Abstract: Background Parents of children with complex, chronic conditions report a desire for continuity of care, but relatively little is known about the ways in which nursing continuity of care occurs and the extent to which it is delivered in the inpatient setting. Objectives The objective of this analysis, which arose from a study on best practices in parent/nurse interactions in the pediatric intensive care unit (PICU), was to explore the delivery of continuity of nursing care in the PICU from the perspective of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
59
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 24 publications
2
59
0
7
Order By: Relevance
“…Our findings are consistent with the few previous studies that have documented the effects of nursing structure on parent response to the experience of a hospitalized infant or child. Parents of children with complex health conditions being cared for in paediatric intensive care units reported that having the same nurses care for their child allowed them to relax at the bedside, whereas having new nurses increased their stress and heightened their vigilance (Baird, Rehm, Hinds, Baggott, & Davies, ). A study of nursing structure in NICUs used a network analysis similar to that used in the current study, finding that when there was a greater number of shifts between repeat nurses, parents had less confidence and trust in the infant's nurse and were less likely to be certain as to which nurse was responsible for their infant's care (Gray et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are consistent with the few previous studies that have documented the effects of nursing structure on parent response to the experience of a hospitalized infant or child. Parents of children with complex health conditions being cared for in paediatric intensive care units reported that having the same nurses care for their child allowed them to relax at the bedside, whereas having new nurses increased their stress and heightened their vigilance (Baird, Rehm, Hinds, Baggott, & Davies, ). A study of nursing structure in NICUs used a network analysis similar to that used in the current study, finding that when there was a greater number of shifts between repeat nurses, parents had less confidence and trust in the infant's nurse and were less likely to be certain as to which nurse was responsible for their infant's care (Gray et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Communication between nurses must include not only the infant's specific technical care needs but also information that improves nurse knowledge about that unique family and infant (Baird et al, ; Siow, Wypij, Berry, Hickey, & Curley, ), potentially enabling consistency of care provision among multiple nurses. There is also evidence in intensive care settings of an inadequate focus on the development of relationship skills with families in crisis compared with the development of the necessary technical skills (Baird et al, ). Improving our ability to provide care focused on relationship building must become as much of a priority as providing excellent care using our technical skills.…”
Section: Discussionmentioning
confidence: 99%
“…42,45 Parents of patients with CCC are often exhausted by the care that they provide at home 46 and remain vigilant at the child’s bedside in the ICU because they are concerned about the lack of continuity and the potential for errors. 6,8,47,48 These families may be more likely to experience organizational problems and also be more stressed by them. Thus, the capacity for the clinical team to build and sustain trusting relationships with families of patients with CCC is critical.…”
Section: Discussionmentioning
confidence: 99%
“…Parents evaluated care quality based on how well nurses knew their infant and the infant's unique characteristics. As reported in Baird et al (2016), parents preferred having consistent nurses and expressed relief when this occurred; parents experienced frustration when faced with frequent new caregivers and felt it necessary to remain vigilant at the bedside. Parents in the Geoghegan et al (2016) study also expressed that finding out which nurse would be caring for their child would either produce the sentiment "Oh thank goodness" or "Oh, my God, this is going to be a hell of…" (p. e499).…”
Section: Respect and Dignitymentioning
confidence: 99%
“…Perhaps one barrier to the implementation of consistent caregivers in the PICU is the nurses themselves. Nurses have indicated that they would prefer not to work with the same patients for multiple shifts because it could create boredom or possible attachment to a patient/family (Butler et al, 2015); many PICU nurses indicated that caring for the same patient repeatedly would not allow them to advance their knowledge or skills (Baird et al, 2016). In addition to respecting parent preferences for care of their infant and increasing satisfaction, neonatal intensive care unit outcomes research has shown that length of stay and duration of mechanical ventilation may be positively impacted by consistent nurse assignments (Mefford and Alligood, 2011).…”
Section: Respect and Dignitymentioning
confidence: 99%